METODE DEMONSTRASI BERBANTUAN ALGA MEDAIR MENINGKATKAN KOMPETENSI PERPINDAHAN PANAS PADA SISWA KELAS V SD NEGERI 02 KESESIREJO SEMESTER 1 TAHUN PELAJARAN 2019/2020 - Biyana Biyana (CV Sintesia, 2023)
The main problem in this research is the low heat transfer in fifth grade students of SD Negeri 02 Kesesirejo, Bodeh District, Pemalang Regency in the subject of Natural Sciences. The teacher uses the Alga Medair-assisted demosntration method, where students demonstrate heat transfer with the help of water media props. While the data analysis technique approach used descriptive analysis to determine the test results and observations (non-test), interactive analysis of the results obtained from the non-test in a qualitative way. This study aims to improve the ability of teachers in the application of interactive learning with the method of demonstration assisted by Alga Medair, to improve the ability of heat transfer material, fifth grade students of SD Negeri 02 Kesesirejo, Bodeh District, Pemalang Regency in Natural Sciences subjects. The results of the study prove that it can improve learning outcomes of basic competencies. Explain the occurrence of heat transfer in class V SD Negeri 02 Kesesirejo, Bodeh District, Pemalang Regency in the 2019/2020 academic year between cycles has increased. In succession (pre-cycle, cycle I, and II) the learning outcomes of class V SD N 02 Kesesirejo, Bodeh District with a pre-cycle average value of 64.60 to 71.80 in cycle I, in cycle II it increased to 77.20. 48.00% classical completeness in the pre-cycle becomes 64.00% in the first cycle, and 80.00% in the second cycle, student activeness reaches 72.00% in the first cycle, increases to 80.00% in the second cycle, student enthusiasm / Student enthusiasm reaches a value of 76.00% in cycle I, becomes 84.00% in cycle II, by applying interactive learning combined with the Alga Medair-assisted demonstration method in grade V SD Negeri 02 Kesesirejo, Bodeh District, Pemalang Regency in Science subjects Science